2010
DOI: 10.1128/jb.01379-09
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Amoeba Symbiont “CandidatusAmoebophilus asiaticus” Reveals Common Mechanisms for Host Cell Interaction among Amoeba-Associated Bacteria

Abstract: Protozoa play host for many intracellular bacteria and are important for the adaptation of pathogenic bacteria to eukaryotic cells. We analyzed the genome sequence of "Candidatus Amoebophilus asiaticus," an obligate intracellular amoeba symbiont belonging to the Bacteroidetes. The genome has a size of 1.89 Mbp, encodes 1,557 proteins, and shows massive proliferation of IS elements (24% of all genes), although the genome seems to be evolutionarily relatively stable. The genome does not encode pathways for de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 133 publications
(164 reference statements)
7
182
0
1
Order By: Relevance
“…These features include reduced genome size, AT bias, and loss of biosynthetic pathways (64,65). In particular, amino acid biosynthetic genes are often lost in obligate symbiotic bacterial genomes (obligate host pathogens and obligate endosymbionts) (64,66,67), where amino acids are obtained from the host environment.…”
Section: Discussionmentioning
confidence: 99%
“…These features include reduced genome size, AT bias, and loss of biosynthetic pathways (64,65). In particular, amino acid biosynthetic genes are often lost in obligate symbiotic bacterial genomes (obligate host pathogens and obligate endosymbionts) (64,66,67), where amino acids are obtained from the host environment.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation has been made when the genome sequence of the amoeba symbiont "Candidatus Amoebophilus asiaticus" has been analyzed. Interestingly, many of the eukaryotic motifs identified in Legionella are also present in this bacterium (Schmitz-Esser et al 2010). Most interestingly, an enrichment analysis comparing the fraction of all functional protein domains among 514 bacterial proteomes revealed that all genomes of bacteria replicating in amoeba were enriched in protein domains that are predominantly found in eukaryotic proteins (Schmitz-Esser et al 2010).…”
Section: The Mobilome Of Legionella Has a Diverse Originmentioning
confidence: 99%
“…Interestingly, many of the eukaryotic motifs identified in Legionella are also present in this bacterium (Schmitz-Esser et al 2010). Most interestingly, an enrichment analysis comparing the fraction of all functional protein domains among 514 bacterial proteomes revealed that all genomes of bacteria replicating in amoeba were enriched in protein domains that are predominantly found in eukaryotic proteins (Schmitz-Esser et al 2010). The most highly enriched domains were ANK repeats, LRR, SEL1 repeats, and Fand U-box domains, all of which are also present in L. pneumophila and L. longbeachae.…”
Section: The Mobilome Of Legionella Has a Diverse Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Per la capacità di sostenerne la sopravvivenza e la crescita e attivare la virulenza dei microrganismi veicolati, è altamente plausibile che le amebe a vita libera rivestano un ruolo preponderante nella proliferazione dei microrganismi nelle reti idriche. La potenzialità ad acquisire una maggiore infettività (46,48,52) dopo la crescita all'interno delle amebe, unitamente alla possibilità che abbiano luogo fenomeni di scambio di materiale genetico (44), conferiscono ai microrganismi a diffusione idrica un notevole vantaggio biologico che è di fondamentale importanza nella loro evoluzione a patogeni umani. È emerso che le amebe a vita libera presenti nelle reti idriche ospiterebbero microrganismi più frequentemente di quanto accada per quelle isolate da sorgenti idriche naturali.…”
Section: Ecologia Delle Amebe a Vita Libera Nelle Reti Idriche E Neglunclassified